2023
DOI: 10.3389/fpsyg.2022.1032384
|View full text |Cite
|
Sign up to set email alerts
|

How do word valence and classes influence lexical processing? Evidence from virtual reality emotional contexts

Abstract: The current study examines the influence of word class (i.e., noun vs. adjective) and valence (i.e., positive vs. negative vs. neutral) on the processing of emotional words under different virtual reality (VR) emotional contexts. To this end, 115 participants performed a modified affect labeling task after experiencing different VR scenarios. Their galvanic skin responses were also examined to further gauge the different effects of VR contexts. The results demonstrated significant main effect for word valence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Additionally, Mahmud et al [50] found that exposure to relaxing virtual environments induced positive emotions and reduced negative The role of VR in eliciting positive emotions was also explored in various contexts. Wang et al [49] demonstrated the role of emotional responses in VR exhibitions, where participants reported feeling pleasure and satisfaction, indicating the potential of VR environments to evoke positive emotions. Additionally, Mahmud et al [50] found that exposure to relaxing virtual environments induced positive emotions and reduced negative emotions, highlighting the potential therapeutic effects of VR in promoting positive emotional experiences.…”
Section: Post-vr Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Mahmud et al [50] found that exposure to relaxing virtual environments induced positive emotions and reduced negative The role of VR in eliciting positive emotions was also explored in various contexts. Wang et al [49] demonstrated the role of emotional responses in VR exhibitions, where participants reported feeling pleasure and satisfaction, indicating the potential of VR environments to evoke positive emotions. Additionally, Mahmud et al [50] found that exposure to relaxing virtual environments induced positive emotions and reduced negative emotions, highlighting the potential therapeutic effects of VR in promoting positive emotional experiences.…”
Section: Post-vr Questionnairementioning
confidence: 99%
“…Chirico et al [53] have highlighted that VR has the potential to elicit both positive and negative emotions, indicating that emotional experiences in VR environments are of a dual nature. Meanwhile, Wang et al [49] have emphasized that the emotional impact of VR is influenced by the specific VR context, as demonstrated by the processing of balanced words. Furthermore, Ślósarz et al [22] have observed an increase in the intensity of positive emotions following VR intervention, compared to the intensity of negative emotions during the post test, indicating a potential positive influence of VR on emotions.…”
Section: Post-vr Questionnairementioning
confidence: 99%